A Missing Link in Undecagold Cluster Chemistry: Single‐Crystal X‐ray Analysis of [Au11(PPh3)7Cl3]. Issue 12 (19th March 2013) - Gutrath, Benjamin S.; Englert, Ulli; Wang, Yutian; Simon, Ulrich
Abstract: Because of quantum‐size effects, molecular gold clusters are promising materials for applications in nanoscience and nanotechnology. Owing to the feasible synthesis of Au11 species out of [Au(PPh3 )Cl], this material is the subject of many investigations, although its full crystal structure including the ligand shell remained unknown. We have been able to obtain the solid‐state structure at atomic resolution, even for the cocrystallized solvent molecules: The composition of the red crystals corresponds to [Au11 (PPh3 )7 Cl3 ]· CH2 Cl2 · 1.5{(CH3 CH2 )2 O}. The gold atoms in the cluster subtend a core of almost C 3 v symmetry derived from a centered icosahedron, which is present in most Au11 species. The mean Au–Au distance amounts to 2.8076 Å and the mean Au–Cl distance to 2.3730 Å; both are in good agreement with comparable data in structurally characterized gold clusters. The mean core diameter, measured between the centers of the gold atoms of opposite sides of the cluster, is about 4.9 Å, and the overall van der Waals diameter can be estimated to 19.8 Å. The optical absorbance of [Au11 (PPh3 )7 Cl3 ] in solution reveals characteristic peaks at 318 and 406 nm and a shoulder between 450 and 550 nm. The peak at 406 nm and the shoulder can also be resolved for the solid. The energy of the first optically active electron transition of ca. 2.0 eV is very close to the theoretically derived data of the HOMO–LUMO gap. In accordance with the literature, only one singlet in the 31 P{ 1 H} NMR spectrum is found at δ = 52 ppm, even at –80 °C. Abstract : Got you! Since 1966, reduction of [Au(PPh3 )Cl] in ethanol represented the easiest large‐scale synthesis of undecagold and gold clusters. However, the full molecular structure of this Au11 cluster remained unclear, and several formulae were published. Now, structure elucidation was successful, which is thought to bring added value from past publications and important impact to new investigations.